Accelerating Infrastructure Development In Post-Pandemic Era - Berawi, Mohammed; Miraj, Perdana; Sari, Mustika (CSID Journal of Infrastructure Development, 2020)
COVID-19 outbreak has contributed a negative effect on the infrastructure sector worldwide. Infrastructure projects need to shut down and put on hold for an unspecified time, as this sector required a high number of workers prone to the virus transmissions. However, the degree of slowdown between countries varies and depends on the severity of pandemic and lockdown conditions. Many countries are having a slowdown in economic growth. This condition has greatly affected the supply and demand sides, making it difficult to predict recovery timelines of on-going and future project development.In response to the COVID-19 pandemic, many governments worldwide launched stimulus plans to recover their economies. The severe impacts of the outbreak need to be addressed through international cooperation. During the pandemic and recession, government expenditure is crucial to driving the economy. Infrastructure projects have been argued as a way to accelerate economic recovery, considering the infrastructure industry is absorbing many workers and driving other supply chain industrial sectors. Therefore, green investment in renewable energy, clean transportation, advanced technologies, and other low-carbon infrastructure projects can stimulate the economy during pandemics and recession.Despite playing a pivotal role in coping with current challenges, not all countries have financial freedom and supporting policies enabling them to invest in infrastructure heavily. Therefore, these countries must prioritize projects that significantly boost income per capita, livelihood improvement, and employment opportunities, particularly for mid to lower-income households. The government is encouraged to pursue the construction of social infrastructures such as healthcare, education, public facilities, and transportation. This attempt is expected to facilitate quick recovery from the pandemic and maintain public services.Most stakeholders associated with the infrastructure sector that suffered from the crisis attempted to create a roadmap, quick wins, and strategic actions to prepare challenges they might face for the next normal. Related stakeholders are highly encouraged to consider digital technology adoption, supply chain redistribution of products and materials, resource allocation of company assets and portfolio, organization restructuring, identification of alternative market opportunities, and collaboration with other parties, including the government, to rebuild the industry. These actions aim to maintain businesses from a growing debt and high-cost recovery during the pandemic.Remote working has catapulted the need to utilize technology further to accelerate infrastructure development and gain maximum benefits for participated stakeholders. The fourth Industrial Revolution (Industry 4.0) enables automation and data exchange within a cyber-system. Digital transformation through big data, machine learning, cloud computing, and other artificial intelligence domain has facilitated real-time working condition between office and site. Advanced technologies also offer a vast potential to improve project performance and increase construction workers' productivity compared to the business as usual approach. We believe that the pandemic urged the utilization of a robust technological innovation in developing infrastructure projects in the post-pandemic era.